Consumer behaviour - Hogg, Gillian (Henry Stewart Talks, 2012)
Changing nature of the consumer, The modern consumer, What a product is, Consumer value, Segmentation, Value and values, Understanding consumers, Confectionary example, Consumer decision making, Types of consumer decision, Situation influences, Problem recognition, Information searches, Influences on searches, Evaluation of alternatives, Decision rules, Brand vs. price, Perceived risk, Types of risk, Reaction to risk, Risk reduction, Influences on purchase, Post purchase
Reviewed at 2020/04/30